2015
DOI: 10.1007/s00128-015-1624-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Heavy Metal Content and Lipid Peroxidation Indicators in the Tissues of the Mussel Crenomytilus grayanus for Pollution Assessment After Marine Environmental Remediation

Abstract: We examined the effects of environmental remediation on the heavy metal concentration and lipid peroxidation activity in the digestive gland and gills of the marine mussel Crenomytilus grayanus. Changes in heavy metal concentrations and lipid peroxidation biomarkers in the tissues of mussels collected at a contaminated site were compared with those obtained from a reference site. Prior to remediation the concentration of Pb, Cu, Cd, Fe and Zn and the levels of malondialdehyde, conjugated dienes and lipofuscin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Giarratono et al (2010) and Stien et al (1998) also found higher levels of Zn in the gills (83.9-280.6 mg/kg) and digestive gland (55.4-102.5 mg/kg) of blue mussels and in digestive gland (124.0-151.0 mg/kg) of Mediterranean mussel, respectively, compared to our findings. Similarly, Belcheva et al (2015) recorded higher levels of Zn in the gills (75.0-272.0 mg/kg) and digestive gland (90.4-229.0 mg/kg) in Mediterranean mussels from a polluted location. Gagnon et al (2006) reported Zn levels of 292.5 mg/kg in the gills and 134.2 mg/kg in the digestive gland of Elliptio complanata mussels, exposed to waste-water plume.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Giarratono et al (2010) and Stien et al (1998) also found higher levels of Zn in the gills (83.9-280.6 mg/kg) and digestive gland (55.4-102.5 mg/kg) of blue mussels and in digestive gland (124.0-151.0 mg/kg) of Mediterranean mussel, respectively, compared to our findings. Similarly, Belcheva et al (2015) recorded higher levels of Zn in the gills (75.0-272.0 mg/kg) and digestive gland (90.4-229.0 mg/kg) in Mediterranean mussels from a polluted location. Gagnon et al (2006) reported Zn levels of 292.5 mg/kg in the gills and 134.2 mg/kg in the digestive gland of Elliptio complanata mussels, exposed to waste-water plume.…”
Section: Discussionmentioning
confidence: 77%
“…found similar Cu levels in the gills (2.7-4.5 mg/kg) and digestive gland (3.0-7.2 mg/kg) of mussels from a commercial mussel farm, while Stien et al (1998) found higher levels of Cu in the digestive gland (8.6-9.7 mg/kg) of caged Mediterranean mussels. Belcheva et al (2015) also reported higher levels of Cu for the gills (7.6-13.4 mg/kg) and digestive gland (12.0-24.9 mg/kg) in Mediterranean mussels from non-polluted locations, while the authors recorded higher levels of Cu in the gills (15.7-448.0 mg/kg) and digestive gland (24.1-89.3 mg/kg) of mussels from a polluted area. Gagnon et al (2006) found Cu levels of 14.3 mg/kg in the gills and 15.4 mg/kg in the digestive gland of Elliptio complanata mussels, exposed to waste-water plume.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effectiveness of the restrictions implemented in the EU has been reflected in the declines of the air emissions recorded from 1990 to 2016 for Pb, Cd, Hg, As, Cu and Zn by 93, 65, 71, 67, 65 and 36%, respectively (EEA, 2018). Regarding industrial and domestic waste, several studies have revealed that environmental remediation actions have led to a reduction of metal levels in mussels (Besada et al, 2014;Belcheva et al, 2015). This is particularly relevant for Pb due to the gradual reduction of the maximum content in gasoline during study period (0.4 g/L in 1987, 0.15 g/L in 1988 and 0.005 g/L in 1999) (RD 1485(RD /1987RD 1728RD /1999) until its complete ban in 2001 (RD 785/2001).…”
Section: Temporal Trends Over Two Decadesmentioning
confidence: 99%
“…However, this dispersion among environmental compartments has accelerated due to the human need to exploit the geological formations where these metal(loid)s have the highest concentrations in confined conditions. Mismanagement of the waste derived from mining extraction (Conesa and Schulin., 2010), together with the lack of control over domestic and industrial waste (Belcheva et al, 2015) accounts for part of the dispersion. This is compounded by other sources of pollution such as river inputs or atmospheric deposition (Jickells, 1995), shipyard areas or eventual spills from ships (Santos-Echeandía et al, 2005) or industries, leading to an increase of metal(loid) concentrations in the different marine environmental matrices (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors had reported the high aptitude of two mussel organs gill and digestive gland in the storage process of heavy metals as Viarengo et al (1990), Sreedevi et al (1992), Amiard et al (1993), Stien et al (1998), Blasco and Puppo (1999), Vlahogianni et al (2007), Peyrot et al (2009), Cooper et al (2010, Giarratano et al (2011), Jebali et al (2014, Belcheva et al (2015), Chandurvelan et al (2015), and Yigit et al (2018).…”
Section: Discussionmentioning
confidence: 99%